(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2016)
In this paper, A new method proposed and coined by the authors as the natural variational iteration transform method(NVITM) is utilized to solve linear and nonlinear systems of fractional differential equations. The new method is a combination of natural transform method and variational iteration method. The solutions of our modeled systems are calculated in the form of convergent power series with easily computable components. The numerical results shows that the approach is easy to implement and accurate when applied to various linear and nonlinear systems of fractional differential equations.